1964
DOI: 10.1126/science.144.3622.1130
|View full text |Cite
|
Sign up to set email alerts
|

Polarographic Investigation of Conjugated Fat-Soluble Vitamins

Abstract: The half-wave potentials of all-trans beta-carotene, all-trans retinol, 13-cis retinol, all-trans retinyl acetate, all-trans retinal, and vitamins D(2) and D(3) were related to the number of double bonds in conjugation. A minimum of three double bonds in conjugation was required before reduction took place at the dropping-mercury electrode. As the number of conjugated bonds increased in the fat-soluble vitamins, the initial reduction took place at a lower half-wave potential. All of the waves were linearly pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1967
1967
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, when conducting the reductive electrolysis at 253 K, it was possible to record up to the transfer of 4e – per molecule, which indicates that the temperature has an effect on the electrochemical reduction of 1 . , There has been some controversy as to how many electrons are involved in the reduction reaction of 1 . Earlier studies by Takahashi and Tachi , and Kuta and Ju , suggested a 4e – reduction process, while Mairanovsky et al, Valentin Pfund et al, and Park suggested a 1e – process.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, when conducting the reductive electrolysis at 253 K, it was possible to record up to the transfer of 4e – per molecule, which indicates that the temperature has an effect on the electrochemical reduction of 1 . , There has been some controversy as to how many electrons are involved in the reduction reaction of 1 . Earlier studies by Takahashi and Tachi , and Kuta and Ju , suggested a 4e – reduction process, while Mairanovsky et al, Valentin Pfund et al, and Park suggested a 1e – process.…”
Section: Resultsmentioning
confidence: 92%
“…33,37 There has been some controversy as to how many electrons are involved in the reduction reaction of 1. Earlier studies by Takahashi and Tachi 10,11 and Kuta and Ju 51,52 suggested a 4e − reduction process, while Mairanovsky et al, 23 Valentin Pfund et al, 24 and Park 14 suggested a 1e − process.…”
Section: Oxidative Cyclicmentioning
confidence: 95%